Uji Aktivitas Antiinflamasi Ekstrak Etanol, Etil Asetat, dan N-heksan Tangkai Daun Kemumu (Colocasia gigantea Hook.f) secara in vitro terhadap Sel Makrofag Peritoneum - Rosi, Devahimer Harsep; Qalbi, Abrar Hafidz; Afriani, Tika (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Kemumu leaf stalks (Colocasia Gigantea Hook.F) are a plant that has many benefits for society, one of which is anti-inflammatory. Inflammation is process in the body to respond to infection or tissue damage. This study aims to test the anti-inflammatory effectiveness of ethanol extract, n-hexane, and ethyl acetate of kemumu leaf stalks in vitro. Kemumu leaf stalks contain flavonoids, alkaloid and tannin which have anti-inflammatory properties. Anti-inflammatory effectiveness testing was carried out on peritoneal macrophage cells to determine the inhibition of NO production in LPS-stimulated peritoneal macrophage cells by quantifying nitrite accumulation in the culture medium using Griess reagent. This research is an experimental study with 5 dose treatments for each extract with 3 replications. The parameters observed included NO production and the percentage of peritoneal macrophage cell inhibition. The results of statistical tests using One Way Anova showed a significant difference in NO levels between the sample group given the extract and the control sample (p=0.000). From the results of the percentage inhibition of NO production in peritoneal macrophage cells, it shows that ethanol extract of kemumu leaf stalks with concentrations of 50 and 100 µg/ml has the best anti-inflammatory effect, namely with NO production of 4.67 and 1.44 µg/ml respectively, and with respective inhibition 80.32% and 89.01% respectively.